"If there is no water, we cannot feed our children": The far‐reaching consequences of water insecurity on infant feeding practices and infant health across 16 low‐ and middle‐income countries. Issue 1 (23rd December 2019) - Schuster, Roseanne C.; Butler, Margaret S.; Wutich, Amber; Miller, Joshua D.; Young, Sera L.; ,
Abstract: Objectives: Infant feeding plays a critical role in child health and development. Few studies to date have examined the link between household water insecurity and infant feeding, and none in a cross‐cultural context. Therefore, we examined the perceived impact of household water insecurity in four domains: breastfeeding, non‐breastmilk feeding, caregiver capabilities, and infant health. Our research was conducted as part of the Household Water Insecurity Experiences (HWISE) study. Methods: We interviewed respondents from 19 sites in 16 low‐ and middle‐income countries (N = 3303) about the link between water insecurity and infant feeding. We then thematically analyzed their open‐ended textual responses. In each of the four domains (breastfeeding, non‐breastmilk feeding, caregiver capabilities, infant health), we inductively identified cross‐cultural metathemes. We analyzed the distribution of themes across sites quantitatively and qualitatively. Results: Water was perceived to directly affect breastfeeding and non‐breastmilk feeding via numerous pathways, including timing and frequency of feeding, unclean foods, and reduced dietary diversity. Water was perceived to indirectly affect infant feeding through caregiver capabilities by increasing time demands, exacerbating disease, undernutrition, and mortality, and requiring greater efficacy of caregivers. Respondents made connections between water challenges and infant health, for example, increased risk of infectious diseases, undernutrition, and mortality. Conclusions: These findings suggest that water presents many, and sometimes unexpected, challenges to infant feeding. By systematically investigating biocultural pathways by which water impacts infant and young child feeding, it will be possible to understand if, and how, water security can be leveraged to improve child nutrition and health.